Numerical Analysis of Thermal Environment of Multi-Functional Vertical Arm Impacted by Gas of Launch Vehicle at Different Altitudes - Yichen Wang; Yifei Su; Guigao Le (Aerospace)
This paper investigates the heat distribution on the movable vertical arm of the CZ-12 launch vehicle within the rocket plume impact field in the three-horizontal test launch mode. A model for the different flight altitudes of rocket plume impact on the different angles of the vertical arm was established based on the three-dimensional Navier–Stokes equations and a realizable <semantics>k−ε</semantics> turbulence model. The numerical results were compared with experimental data and schlieren images from literature to verify the effectiveness and accuracy of the established numerical model. The results show that when the flight altitude of the rocket is between 30 m and 40 m, the worst heat environment occurs on the front and bottom of the vertical arm. Before reaching a flight altitude of 30 m, a smaller rotation angle of the vertical arm leads to higher maximum temperatures at these two regions. After reaching a flight altitude of 40 m, a larger rotation angle of the vertical arm results in higher maximum temperatures. The top of the lower frame structure is not directly affected by the rocket plume before reaching a flight altitude of 30 m. After reaching a flight altitude of 40 m, a smaller rotation angle of the vertical arm results in higher heat loads on the frame. The results of this study can provide a basis for designing targeted thermal protection for vertical arms. They also contribute a new idea for reducing the thermal load on the vertical arm, which is to rotate the vertical arm to the appropriate angle according to the rocket takeoff altitude. Meanwhile, these research findings will supply a relative reference for researchers who are concerned about other facilities in the surrounding area.